Analisis Komunikasi Pemasaran Aston Denpasar Hotel & Convention Center dalam Membentuk Citra Positif - Ni Kadek Sri Mirayani; I Gusti Ngurah Oka Widjaya; Ni Putu Lilik Widyayanthi; Putu Wira Parama Suta (Yayasan Literasi Sains Indonesia, 2025)
Aston Denpasar Hotel & Convention Center is one of the hotels located in the center of Denpasar. This hotel has the challenge of forming a positive image as a differentiator from other hotels located around Denpasar City with similar facility offerings. This study aims to analyze the marketing communication used by the hotel in forming a positive image in the community and target market. This type of research is qualitative descriptive research. Data was collected through observation, interviews and documentation. The results of the study show that Aston Denpasar Hotel & Convention Center implements a digital marketing strategy. This is realized by using a website, Instagram, collaboration with national media, collaboration with influencers in introducing products. In addition, the hotel also implements a Corporate Social Responsibility (CSR) program as one proof that the hotel cares about the surrounding community so that it can strengthen the hotel's positive image. The marketing communication implemented by Aston Denpasar Hotel & Convention Center is very good, it just still needs some improvements such as the use of storytelling in promotional content, the use of more consistent hashtags, and being more interactive in promotional activities.